A Survey of Substance Misuse Prevalence and Management in Patients Admitted to a Male Acute Ward, a Female Acute Ward, and a Male Psychiatric Intensive Care Unit in KMPT - Faizaan Syed; Ifeoma Neye-Akogo; Rubayat Jesmin; Shantala Satisha (BJPsych Open)
Aims: Substance misuse is a common comorbidity in severe mental illness, contributing to increased morbidity and poorer clinical outcomes. Effective management requires accurate documentation and structured interventions. However, existing practices in psychiatric inpatient care are often inconsistent, necessitating a thorough evaluation to inform service development.